Digital photography of digital imaging and communications in medicine -- 3 images from computers in the radiologist's office...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Chin H; Klepac D; Ernst RD; Kawashima A; Tamm EP; Reyna D; Sandler CM (Journal of Digital Imaging)
To fully take advantage of the widespread use of digital imaging systems and to update and eliminate redundant steps involved in medical radiographic publication, we present our experience of processing Digital Imaging and Communications in Medicine (DICOM)-3 digital images from the point of acquisition to the point of publisher-ready radiographic images without intervening hardcopies. Copyright (c) 1999 by W.B. Saunders Company